2011
DOI: 10.1186/1471-2415-11-30
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated fusariosis and endogenous fungal endophthalmitis in acute lymphoblastic leukemia following platelet transfusion possibly due to transfusion-related immunomodulation

Abstract: BackgroundTo report a case of disseminated fusariosis with endogenous endophthalmitis in a patient with acute lymphoblastic leukemia. Transfusion-associated immune modulation secondary to platelet transfusion could play an important role in the pathophysiology of this case.Case PresentationA 9 year-old male with acute lymphoblastic leukemia complicated by pancytopenia and disseminated Intravascular coagulation was given platelet transfusion. He developed disseminated fusariosis and was referred to the ophthalm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…in immunocompromised or neutropenic patients. Fourteen cases were previously reported in more recent literature (from 2002 to present): twelve in haematology patients (six acute myeloid leukaemia or myelodysplastic syndrome, five acute lymphoblastic leukaemia, one Hodgkin lymphoma), one liver transplant and one patient affected by diabetes mellitus (Table ) . In the fourteen cases, the infection was limited to the eye in three patients including the eyelids and skin surrounding the eyes, while it was disseminated (with eye involvement) in the remaining 11 cases: skin (10 cases), blood (7 cases), lungs (4 cases), CNS (2 cases) and bone (1 case).…”
Section: Case Discussion and Literature Reviewmentioning
confidence: 96%
See 4 more Smart Citations
“…in immunocompromised or neutropenic patients. Fourteen cases were previously reported in more recent literature (from 2002 to present): twelve in haematology patients (six acute myeloid leukaemia or myelodysplastic syndrome, five acute lymphoblastic leukaemia, one Hodgkin lymphoma), one liver transplant and one patient affected by diabetes mellitus (Table ) . In the fourteen cases, the infection was limited to the eye in three patients including the eyelids and skin surrounding the eyes, while it was disseminated (with eye involvement) in the remaining 11 cases: skin (10 cases), blood (7 cases), lungs (4 cases), CNS (2 cases) and bone (1 case).…”
Section: Case Discussion and Literature Reviewmentioning
confidence: 96%
“…3,6,[22][23][24] Although less common, disseminated infections involving the eye, joints, CNS and heart valves have been reported. [15][16][17][18][19]25 The largest contemporary series of Fusarium endophthalmitis outcomes was reported by Troke et al, (n = 24) who found a 63% overall response rate when patient received treatment with systemic and topical voriconazole with or without vitrectomy. 26 However, this case series described patients with mostly exogenous infections and did (Table 1).…”
Section: Case Discussion and Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations